Economic transformation and the revaluation of human capital - Hungary, 1986-1999 - Gabor Kertesi; Janos Kollo (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2001)
The paper analyses the evolution of relative wages using individual wage data, and the contribution of skills to productivity using firmlevel information from Hungary, 1986-99. Its main conclusion is that skills obsolescence was, and still is, an important aspect of postcommunist transition. The data suggest a general rise in the returns to education between 1989 and 1992. This, the paper argues, was just a mirror image of the collapse of demand for unskilled labour in a period of deep crisis when technological change was minimal, and the forces of the market just started to work. When market institutions were already at work, and modern technologies were implemented on a massive scale, the general appreciation of education stopped but the returns to experience continued to decline. Young and educated workers are paid increasing wages and their skills are estimated to yield higher productivity returns, especially in a modern environment. By contrast, neither productivity nor wages grew for the older cohorts of educated workers after 1992.
Keywords: 330